2022
DOI: 10.1177/07334648221120080
|View full text |Cite
|
Sign up to set email alerts
|

Job Demands May Determine Cognitive and Physical Aging After Retirement

Abstract: During adulthood, we spend most of our time and efforts at work. However, the impact of employment in aging is poorly explored. Our study addressed how job demands can affect aging after retirement. We have developed a descriptive observational study carried out in 367 older adults with a mean age of 73.9 years (66.5% women and 33.5% men), measuring cognition and functional status. Our results demonstrate that older adults who had high mental demands in their jobs, show better scores in cognition. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Similarly, the correlational analyses highlighted that those who exhibited better CR (i.e., educational attainment, work occupation, and total CR index) also showed a better speed of processing assessed through the TMT-A. Besides, following previous studies (e.g., Calatayud et al, 2022), formal schooling and work occupation were significantly associated with cognitive flexibility and shifting skills (i.e., assessed through TMT-B-A), suggesting that those who were more educated and performed more cognitively demanding jobs empowered their executive functions during their lifespan. Moreover, following Ruiu et al (2022), a small and positive significant relationship has been found between perceived physical health and the CRIq-Hobby measure, suggesting that those who were more engaged with cognitively and physically demanding leisure activities also felt physically better.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Similarly, the correlational analyses highlighted that those who exhibited better CR (i.e., educational attainment, work occupation, and total CR index) also showed a better speed of processing assessed through the TMT-A. Besides, following previous studies (e.g., Calatayud et al, 2022), formal schooling and work occupation were significantly associated with cognitive flexibility and shifting skills (i.e., assessed through TMT-B-A), suggesting that those who were more educated and performed more cognitively demanding jobs empowered their executive functions during their lifespan. Moreover, following Ruiu et al (2022), a small and positive significant relationship has been found between perceived physical health and the CRIq-Hobby measure, suggesting that those who were more engaged with cognitively and physically demanding leisure activities also felt physically better.…”
Section: Discussionsupporting
confidence: 61%
“…Assuming an applied viewpoint, as suggested by Calatayud et al (2022), these results encourage the promotion of specific multidomain trainings aimed at boosting both physical reserve and cognitive health in later lifespan through regular and moderate physical exercises (e.g., walking, aerobic exercises, gardening), cognitively demanding individual activities (e.g., reading a book, playing a musical instrument), and leisure activities empowering both the cognitive and social functioning (e.g., hobbies implying novel information processing such as learning a second language or to use a computer, playing bridge). This kind of intervention would be particularly useful for physically inactive older individuals who are more at risk of developing cognitive decline (Li et al, 2023) and for those who performed high physically demanding jobs but with low cognitive demands, because they are more at risk to exhibit poorer cognition (e.g., less efficient executive functions) and lower performance in activities of daily living (Calatayud et al, 2022). In this context, our study confirms the pivotal role played by regular ambulation, which was previously found very beneficial in terms of successful aging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the univariate analyses, it was demonstrated a better nutritional status among those who are retired and working. Literature shows that work life activities, among older adults, are significantly associated with cognitive [32], depression, and other health-related outcomes [33]. In contrast, higher PR for nutritional risk was demonstrated among those who reported being non-users of alcohol.…”
Section: Discussionmentioning
confidence: 99%